Correction to: Temporary materials: comparison of in vivo and in vitro performance. - Sari, Tuğrul; Usumez, Aslihan; Strasser, Thomas; Şahinbas, Abdurrahman; Rosentritt, Martin (My University, 2021)
A Correction to this paper has been published: https://doi.org/10.1007/s00784-021-04067-4.